Health and Safety Law - Stranks, Jeremy W. (Harlow : Prentice Hall, 2005)
Covering all major UK and EU legislation concerning occupational health and safety, this text, written by Jeremy Stranks, is an up-to-date guide to the NEBOSH syllabus.
Previous ed.: 2001.
Includes bibliographical references (p. 427-429) and index.
Keywords: Industrial hygiene -- Law and legislation -- Great Britain; Industrial safety -- Law and legislation -- Great Britain; Law